PENGEMBANGAN BAHAN AJAR MENULIS LAPORAN OBSERVASI PADA MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UNIVERSITAS JAMBI - Andiopenta Purba (Universitas Batanghari Jambi, 2017)
This study aimed to describe; (1) The product feasibility report writing instructional materials observation, (2) the quality of the layout and appearance of the observation report writing teaching materials, and (3) the effectiveness of teaching material written observation report. Model applied research and development is a model of the Borg and Gall. To test the model used efektivis Before-After Experiments design and experiment design Posttest-Only Control, as well as using different test techniques statistical t-test. The results of the study include; Feasibility of this model, content, presentation, and the accuracy of the use of language is very good category. Limited scale testing showed the use of the product in terms of learning motivation of students increased 25%, creativity 23%, and 22% of learning outcomes. On a limited scale testing by t-test, for motivation learn t-count of 7135, and the t-table with a significance level of 2.306 to 0:05 (7135> 2306). Likewise, the creativity of students (7126> 2306) and learning outcomes (9.368> 2.306. From the test results on a limited scale seen that the effect of the use of the product in terms of learning motivation of students increased 12:31, creativity 0.69, and learning outcomes 19:30. Eefektivitas products on a large-scale testing wide through t-test, for motivation learn t-test of 52.43, and a t-table with a level of significance of 0.05 for 2021 so that (52.43> 2,021). Similarly, the creativity of the students (89 998> 2,021) and learning outcomes (79 974> 2021 ), so the hypothesis is accepted. the conclusion is: (1) Model teaching material to write a report on the observation produced in research and development is feasible to use in the course of writing, so it can be used in order to improve learning outcomes in the course of writing, especially on topic to write a report on the observation (2) Model teaching materials written report on the results of interesting observations in terms of the layout and appearance of, so that students are motivated to use them and to increase their creativity in writing skills. (3) Model these materials effectively used preformance faculty and students take courses in writing skills, in this case on the topic of writing a report on the observation.Keywords: development, instructional materials, writing, report observations